A Review on The Spatial Mining - Ghazala Shireen (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Public and confidential associations have heritage or then again functional spatial information bases or non-spatial information bases, which are likewise some ways or another connected to a spatial data set or a spatial significance. Notwithstanding mission related information bases, these associations either have or access a few information bases containing like registration, financial, security, picture, interactive media, factual data for arranging, insight, choice and strategy making. The lengthy size of these informational indexes makes it hard to look for significant examples or connections among information. Spatial information mining is the course offending fascinating and already obscure, however possibly valuable examples from huge spatial datasets. This paper centers around Procedures and the special highlights that recognize spatial information mining from old style information mining, at long last it recognizes areas of spatial information mining where further examination is required.